2019
DOI: 10.4067/s0717-95022019000100082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bone Substitute β-TCP Block for Maxillofacial Reconstruction

Abstract: The aim of this study was to characterize a commercial beta tricalcium phosphate (β-TCP) block allograft for use in maxillofacial reconstruction, evaluating its homogeneity, porosity and mineralization. Two commercial 5 x 5 x10 mm chronOS Vivify β-TCP blocks were used, which were evaluated by a STEM SU-3500 variable pressure scanning electron microscope (SEM-STEM) (Hitachi, Japan). For the semi-quantitative microanalysis of elements, the QUANTAX 100 energy dispersive x-ray spectrometer detector (EDX) (Bruker, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…In groups 1 and 2 the repair was endochondral (indirect) and in group 3 (distance between the bone ends of 8 mm) there was no fracture consolidation; the gap was comprised mainly of fibrous tissue with abundant fibroblasts, without osteoplastic integration. On the same hand, in groups 1 and 2 bone formation in the lateral area of the defect was observed clinically, maybe related to the contact of this area with the periosteal tissue, as related by Alister et al [20]; in the 8 mm bone gap this bone repair was not observed.…”
Section: Discussionmentioning
confidence: 64%
“…In groups 1 and 2 the repair was endochondral (indirect) and in group 3 (distance between the bone ends of 8 mm) there was no fracture consolidation; the gap was comprised mainly of fibrous tissue with abundant fibroblasts, without osteoplastic integration. On the same hand, in groups 1 and 2 bone formation in the lateral area of the defect was observed clinically, maybe related to the contact of this area with the periosteal tissue, as related by Alister et al [20]; in the 8 mm bone gap this bone repair was not observed.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, in the struts of both HC-Ss ( Figure 1 e) and HC-Rs ( Figure 1 f), micropores were present between the spherical aggregates consisting of scale-like crystals. Many researchers previously demonstrated that micropores improved osteogenesis [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Therefore, the micropores in the HC-Ss and HC-Rs may also contribute to bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Macro/microporosity is one of the main factors that affect the resorption of β -TCP because it allows the growth of blood vessels and osteocytic dendrites through the graft [ 47 ]. The reduced macro/micropore size can decrease bone substitution and regeneration [ 48 ]. In the β -TCP group, the presence of osteoclasts and degradation of the matrix in both the central and peripheral zones were noted at 4 and 8 weeks, which is consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%